Aster brevicaulis (Asteraceae, Astereae), a new species from western Sichuan, China - Xiao, Jia-Wei; Liao, Jun-Jie; Li, Wei-Ping (Phytotaxa, 2019)
Aster brevicaulis W. P. Li (Asteraceae, Astereae), a new species from Sichuan, China, is illustrated and described. Morphological data and a phylogenetic analysis based on a combined nuclear DNA ITS and ETS dataset suggest that A. brevicaulis is a separate species closely related to A. tongolensis. The new species differs from the latter by having stems only 2–15 (22) cm long, without stolons, phyllaries 5-seriate, and pappus 4–5 mm long. Cytological observation shows that the new species is diploid with 2n = 2x = 18 =16m + 2sm.